2010
DOI: 10.1007/s12289-010-0883-0
|View full text |Cite
|
Sign up to set email alerts
|

Surface finish effect on the anodizing behaviour of Al-Si components obtained by sub-liquidus casting process

Abstract: The aim of this study was to investigate the hard decorative anodizing components of A357 aluminium alloy, obtained in semisolid state by Sub Liquidus Casting® process, to improve its tribological properties and corrosion resistance.Components were heat treated in order to modify the shape and distribution of the eutectic silicon phase. The influence of shot peening pre-treatment on anodizing process was evaluated. Surface modifications were investigated as they might have beneficial effects on the wear and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…Upon increasing the content of defects in the oxide layer, the galvanic corrosion beneath the oxide surface was enhanced. Similar results were found by Chaukea et al [ 41 ] and Menargues et al [ 42 ]…”
Section: Influence Of the Chemical Composition And Microstructure Of ...supporting
confidence: 92%
“…Upon increasing the content of defects in the oxide layer, the galvanic corrosion beneath the oxide surface was enhanced. Similar results were found by Chaukea et al [ 41 ] and Menargues et al [ 42 ]…”
Section: Influence Of the Chemical Composition And Microstructure Of ...supporting
confidence: 92%
“…With an increase in the defect content within the oxide layer, galvanic corrosion beneath the oxide surface was observed to intensify. In their study, Chaukea et al [48] and Menargues et al [49] reported similar findings.…”
Section: Silicon Particlessupporting
confidence: 56%
“…Anodising, which is an electrochemical process, is one of the most extensively used methods to improve the surface performance of aluminium alloys such as corrosion and wear resistance and aesthetic property. Previous studies have revealed that the anodised layer and its performance is strongly influenced by anodising process [2,3], surface condition [4,5], alloying elements [4,6] and microstructure [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%